2010
DOI: 10.1109/tns.2010.2053049
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Contacts on Electric Field in an Au/(CdZn)Te/Au Detector: A Simulation

Abstract: We report our simulations on the influence of contacts on charge collection in semi-insulating (CdZn)Te with Au contacts under radiation flux, employing simultaneous solutions of the drift-diffusion and Poisson equations. The type of the space charge and the distribution of the electric field in the Au/(CdZn)Te/Au structure at high fluxes reflect the combined influence of charge generated by band bending at the electrodes, and from photogenerated carriers trapped at deep levels. We show that the space charge o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…In detector-grade CdTe-based materials, the density of the mid-gap level is very low ( [ 19 ]. Simultaneously, the captured cross-sections of the mid-gap levels are typically less than [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…In detector-grade CdTe-based materials, the density of the mid-gap level is very low ( [ 19 ]. Simultaneously, the captured cross-sections of the mid-gap levels are typically less than [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…A limited amount of band bending in the current-voltage (I-V) characteristic can be present during routine detector operation [2]. A classical model to describe I-V curves of barrier contacts is diffusion theory proposed by Schottky [3].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, however, experimental findings and simulations have shown that the electric field follows a nonconstant, non-linear shape inside detectors in most of the conditions, [8][9][10] suggesting the need to search for a more general method to reconstruct its spatial distribution.…”
mentioning
confidence: 99%